Musik Shalawat Hadrah dan Transformasi Jiwa Anak Usia Sekolah Dasar: Studi Kasus di Yogyakarta: Shalawat Hadrah Music and the Transformation of the Souls of Elementary School-Aged Children: A Case Study in Yogyakarta - Ichsan, Ahmad Shofiyuddin (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2026)
Throughout history, humans have always sought to achieve happiness and avoid suffering through various means, including religion, which constructs the souls of its adherents into perfect individuals, one of which is through the medium of religious music. This study examines in depth the role of shalawat hadrah music as a medium for soul transformation in elementary school-aged children, especially in Yogyakarta, where this phenomenon is increasingly popular as Islamic entertainment that not only entertains but also supports their spiritual, emotional, and cognitive development. A qualitative approach was applied with a purposive sampling technique to the main subjects, namely hadrah-maniacal children, their parents, and the surrounding community. Primary data were obtained through in-depth interviews and participant observation, while secondary data from literature studies were validated through source triangulation to ensure validity, and analyzed using the Miles and Huberman model, which includes data reduction, presentation, and conclusion drawing. The research results reveal that shalawat hadrah music combines its historical function as a means of da'wah since the 13th century with significant contemporary benefits, such as the maturation of the right-left brain balance to increase emotional sensitivity and social interaction skills, strengthening solidarity between people through increasing the enthusiasm for learning and reciting the Koran, inspiring feelings of deep love for God and the Prophet Muhammad Saw, as well as spiritual entertainment that organically instills the values ​​of monotheism, noble morals, and religious awareness from an early age.